What Does the Camera Communicate? An Inquiry into the Politics and Possibilities of Video Research on Learning. (March 2016) - Vossoughi, Shirin; Escudé, Meg
Abstract : This piece explores the politics and possibilities of video research on learning in educational settings. The authors (a research–practice team) argue that changing the stance of inquiry from surveillance to relationship is an ongoing and contingent practice that involves pedagogical, political, and ethical choices on the part of researchers and educators. This discussion is grounded in ethnographic data collected in an equity‐oriented, after‐school program organized around science, engineering, and arts education.